Annual and monthly runoff analysis in the Elqui River, Chile, a semi-arid snow-glacier fed basin - Balocchi, Francisco; Pizarro, Roberto; Meixner, Thomas; Urbina, Fernando (Tecnología y ciencias del agua, 2017)
Balocchi, F., Pizarro, R., Meixner, T., & Urbina, F. (November-Â Â  December, 2017). Annual and monthly runoff analysis inÂ Â  the Elqui River, Chile, a semi-arid snow-glacier fed basin.Â Â  Water Technology and Sciences (in Spanish), 8(6), 23-35,DOI:Â Â  10.24850/j-tyca-2017-06-02.Â Â Climate change and its relationship to temperature areÂ Â  critical factors affecting glaciers, especially when populationsÂ Â  depend on these ice reservoirs. The use of the precipitationrunoffÂ Â  coefficient in semi-arid, mountainous regions thatÂ Â  are fed by glaciers can lead to important findings aboutÂ Â  how glacial melt responds to climate change. This studyÂ Â  analyzed 40 years of monthly and annual precipitationÂ Â  and runoff data (1970-2009) from four sub-basins of theÂ Â  Elqui River (29° 27'- 30° 34' S and 71° 22'- 69° 52' W), inÂ Â  the Coquimbo region of Chile. The Elqui basin has a rainsnow-Â Â  glacial melt regime. The areal average rainfall wasÂ Â  estimated using the Thiessen polygon method. GumbelÂ Â  and Goodrich probability distribution functions and theÂ Â  Log-Normal Probability Density Function (PDF) were usedÂ Â  to understand the temporal behavior of precipitation andÂ Â  streamflow. The data-time behavior and PP Q-1 coefficientsÂ Â  were also analyzed. And the Mann-Kendall (MK) test wasÂ Â  used to compare the results. No trends were found for flow,Â Â  while a negative trend in rainfall was identified. The summerÂ Â  flows were notable, which remained constant. In spite of theÂ Â  differences between the PP Q-1 coefficient and the MK test,Â Â  the flow clearly does not come from rainfall but rather fromÂ Â  glacial melt. Â Â Â